1998
DOI: 10.1177/004051759806801207
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Scouring with Enzymes, Organic Solvents, and Caustic Soda on the Properties of Hydrogen Peroxide Bleached Cotton Yarn

Abstract: Three different scouring methods are applied to open-end and ring spun yarns prior to hydrogen peroxide bleaching with and without metal ions present. The scouring procedures include a penetrating treatment with aqueous sodium hydroxide solution, a nonswelling solvent extraction, and a fiber surface-affecting treatment with pectinase enzymes. Properties of the treated yarns and fiber damage are studied after each process step. Conventional scouring with sodium hydroxide followed by peroxide bleaching causes th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(32 citation statements)
references
References 5 publications
0
31
0
1
Order By: Relevance
“…Since oxidative damage of cellulose may occur after bleaching, the question is whether or to what degree it is actually necessary to completely oxidize the pigments present in fiber and to remove all noncellulosic matter for satisfactory results. It is well documented in the literature that fiber damage does not reflect through a decrease in fiber tensile strength until a considerable cellulosic chain scission has occurred (Buschle-Diller et al 1998).…”
Section: Resultsmentioning
confidence: 99%
“…Since oxidative damage of cellulose may occur after bleaching, the question is whether or to what degree it is actually necessary to completely oxidize the pigments present in fiber and to remove all noncellulosic matter for satisfactory results. It is well documented in the literature that fiber damage does not reflect through a decrease in fiber tensile strength until a considerable cellulosic chain scission has occurred (Buschle-Diller et al 1998).…”
Section: Resultsmentioning
confidence: 99%
“…From the changes in whiteness of jute fiber, it can be concluded that TAED/H 2 O 2 system bleaching could be conducted at lower temperature with mild alkaline condition (pH 8) and much more effective in removal of colored matters than that of conventional H 2 O 2 bleaching. It is well documented in the literature that fiber damage does not reflect through a decrease in tensile strength until a considerable cellulosic chain scission has occurred [13]. Therefore, the degree of polymerization (DP) of jute fiber was measured before and after different bleaching treatments to estimate the damage on jute fibers during bleaching, and the results were shown in Table I.…”
Section: A Effect Of Bleaching On the Properties Of Fibermentioning
confidence: 99%
“…In further bleaching with hydrogen peroxide, it was established that a better degree of whiteness can be attained on alkaline scoured sample than on the bioscoured one, however, it need to be taken into account that alkaline scoured fibred are very sensitive to oxidative damage during bleaching. More significant damage occures compared to the samples scoured with pectinases (Buschle-Diller et al, 1998). Several researchers examined the possibilities of combining bioscouring with previous and following procedure.…”
Section: Influence Of Bioscouring On Further Finishing Proceduresmentioning
confidence: 99%